Expressão imuno-histoquímica dos marcadores angiogênicos CD105 (endoglina) e CD34 em hemangiomas e granulomas piogênicos orais - Vasconcelos, Marcelo Gadelha (2008)
Angiogenesis, a fundamental mechanism in tumor development, is used for differential diagnosis and prognosis purposes in various neoplasias of the head and neck. This study proposes to assess angiogenic activity using immunohistochemical expression by anti-CD105 and anti-CD34 antibodies in 20 cases of hemangiomas and 20 cases of oral pyogenic granulomas, in addition to determining the usefulness of these markers as one of the differential diagnosis resources for these two oral lesions. The results showed no statistically significant difference between microvascular count (MVC) means determined by anti-CD105 (p = 0.803) and anti-CD34 (p = 0.279) antibodies. The mean number of vessels obtained by MVC in the oral hemangiomas immunostained by anti-CD105 and anti-CD34 was 18.75 and 59.72, respectively, whereas in the oral pyogenic granulomas, the mean number was 20.22 and 48.09 respectively. It was also shown that CD34 was more effective than CD105 in identifying blood vessels. However, it must be pointed out that the anti-CD105 antibody seems to be more related to vascular neoformation. Overall, this assay reinforces the role of angiogenic factors in the etiopathogenesis of hemangiomas and oral pyogenic granulomas, but the results showed that angiogenesis quantification cannot be used as a differential diagnosis parameter between the two lesions analyzed